THE GENDER, POLITIC ISSUE, AND POLITICAL PARTIES ROLE FACTOR ON FEMALE CANDIDATE ELECTION - Hamdi Muluk (Jurnal Psikologi, 2006)
The aim of this study is to know the probability for female candidates for having support from femalevoters than male candidates, the effect of gender role idelogy and level of gender group identity to thesupport for female candidates, and between the four independen varibles, which one that would be thebest predictor for female candidates for 2004 general election. The result shows that there is nodifferences of probability between male and female candidates to be choosen by female voters and thereis no differences also in gender role idelogy and gender group identification for voting the male andfemale candidates. Then, this research also shows that female voters behavior can’t be predicted by thosevariables. The suggestion for the next research is to fix the way sampel is being collected, get morefocused on male participants, enhance other variables such as gender stereotype and involving thecognitive process in voting behavior.Key words: gender, identification